Benjamin Franklin : a biography - Clark, Ronald William (London : Phoenix Press, 2001)
A biography of the eighteenth-century American businessman, diplomat and scientist, with references and a bibliography.
"A Phoenix Press paperback"--T.p. verso.
First published: London : Weidenfeld & Nicolson, 1983.
Includes bibliographical references (p. 483-499) and index.
Booklist.
Adult
Keywords: Franklin, Benjamin, -- 1706-1790.; Franklin, Benjamin, -- 1706-1790.; Printers -- United States -- Biography; Scientists -- United States -- Biography; Statesmen -- United States -- Biography; Printers -- Biography; Scientists -- United States -- Biography; Statesmen -- United States -- Biography